To Grow Single Crystals of 6061 Alumunium Alloy - Harsono Wirjosumarto (Journal of Mathematical and Fundamental Sciences, 1965)
Abstract. Single crystals of 6061 alumunium alloy can be produced by "strain anneal" method from wire  of 2mm diameter. With this method 70% of the test specimens grown into single crystals of length of 2.5 cm. Ichtisar. Kristal tunggal dari paduan aluminium 6061 dapat dihasilkan dengan tjara "strain anneal" dari kawat jang berdiameter 2 mm. Dengan tjara ini 70% dari kawat-kawat tersebut tumbuh mendjadi kristal tunggal jang pandjangnja 2,5 cm.